What does Dakpai Maksim do when he sings sygyt? A preliminary investigation of one throat singer’s personal style - Van Tongeren, Mark (The New Research of Tuva, 2017)
Famous Tuvan throat singers of the twentieth century continue to receive attention by today’s singers. After considering the sources from the Soviet era that are currently (un)available as recordings, the author analyses a single song with sygyt throat singing by Dakpai Maksim (1921–1993). “Karalangny berem ezhi” (Give me your Karala, my friend) was published by Melodiya in 1968 and later appeared on the website of Alan Lomax’s Cultural Equity project. The author presents evidence that Dakpai was skillfully singing text with a simultaneous overtone melody and that the singer deliberately used harmonics that are avoided by most throat singers. He also analyzes a number of melodic patterns that are common in Tuva, but interpreted in his own unique way by Dakpai.
Keywords: Throat singing; Dakpai Maksim; musical analysis; khöömei; Tuvan music; ethnomusicology; sygyt